The European Convention on Human Rights - Ovey, Clare; Jacobs, Francis Geoffrey, 1939- (Oxford [u.s.] : Oxford University Press, 2010)
Fifty years after the founding of the European Court of Human Rights it has dispensed more than 10,000 judgments and affects the lives of over 800 million people. The fifth edition of Jacobs, White & Ovey: The European Convention on Human Rights provides a clear and concise explanation of this increasingly important area of the law. Examining each of the Convention rights in turn, this book lays out the key principles relevant to both Human Rights students and practitioners. Fully updated with all the significant developments of the last four years, it offers a valuable synthesis of lively author commentary and carefully selected case law. By focussing on the European Convention itself rather than its implementation in any one member state this text may be counted as essential reading for all those interested in the work of the Strasbourg organs, while a revised structure ensures the book now maps even more closely to European Human Rights courses. The European Convention on Human Rights offers an accessible overview of Convention law and practice for scholars, lawyers and policy makers. It offers a comprehensive understanding of the work of the Strasbourg Court in interpreting and applying the Convention.
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Human rights -- Europe